Coronary Artery Sequel of Kawasaki Disease in Adulthood, a Concern for Internists and Cardiologists - Anggoro B Hartopo; Budi Y Setianto (Acta Medica Indonesiana)
Young adults suffered from acute cardiac event, such as acute coronary syndrome, ischemic-associated arrhythmia and sudden death, are frequently encountered without known etiology and significant risk factors. Coronary vasculitis due to Kawasaki disease contributes to be a risk factor in young adult population to develop acute coronary event. Afflicted predominantly during childhood, Kawasaki disease gives rise to vasculitis of coronary artery which becomes major concern since it leads to coronary aneurysm and stenosis. Self-limited nature of Kawasaki disease make those suffered in childhood survive into adult life. Accelerated coronary atherosclerosis in the Kawasaki disease-related lesion occurring in young adult and subsequent acute coronary syndrome and sudden death in this population are devastating impacts of the sequel of Kawasaki disease. It is expected that internists and adult cardiologists become familiar with this sequel and provide better care for the patients.